P099 HOSPITALIZATIONS FOR IBD THROUGHOUT THE WORLD: A SYSTEMATIC REVIEW WITH TEMPORAL ANALYSES. (7th February 2019) - Windsor, Joseph W; Buie, Michael; Coward, Stephanie; King, James A; Quan, Joshua; Underwood, Fox; Panaccione, Remo; Seow, Cynthia; Kaplan, Gilaad
Abstract: Background: The prevalence of the inflammatory bowel diseases (IBD), consisting of Crohn's disease and ulcerative colitis, now exceeds 0.3% in North America, Europe, and Oceania, and has been reported as high as 0.7% in some nations within those regions. Conversely, in newly industrialized countries in South America, the Middle East, and Asia, both the incidence and prevalence of IBD is rapidly rising. Following the advent of biologics, many countries report trends of decreasing hospitalizations per IBD patient, but, even with modern methods of treatment, it is not clear if reduced hospitalizations per patient translates to an overall reduction in population-level hospitalizations. Aim: To analyze global trends of all-cause hospitalizations due to persons with IBD. Methods: We conducted a systematic review of MedLine and Embase to identify population-based studies reporting hospitalization rates (or crude hospitalizations) after the year 2000 with at least five years of data. Previous systematic reviews and meta-analyses were excluded, but their references were searched for additional studies. World Bank census data were used for annual population values. Log-linear models were used to calculate average annual percentage change (AAPC), with associated 95% confidence intervals (CI). Results: 7, 782 abstracts were identified; 663 articles underwent full-text review, including seven from grey literature search; data were extracted from 52 studies; and, 17 studies were included in the final time trend analysis. Hospitalization rates were analyzed for 34 countries (table 1, Figure 1). Within North America, hospitalizations for IBD are decreasing in Canada (AAPC: −2.38; 95% CI: −2.55, −2), but increasing in the USA (AAPC: 2.4; 95% CI: 1.5, 3.31). Hospitalization rates are also divergent in Europe with some countries reporting decreasing (e.g., Sweden, AAPC: −2.35; 95% CI: −2.87, −1.84), increasing (e.g., Germany, AAPC: 2.12; 95% CI: 1.76, 2.47), or stable (e.g., France, AAPC: −0.11; 95% CI: −0.41, 0.2) rates. In contrast, newly industrialized countries outside the Western world have the lowest hospitalization rates (Figure 1), but those rates are rapidly increasing in South America (e.g, . Mexico, AACP: 3.67; 95% CI: 2.8, 4.55), the Middle East (e.g., Bahrain, AAPC: 8.25; 95% CI: 5.58, 10.99), and Asia (e.g., China, AAPC: 16.44; 95% CI: 11.84, 21.23). Conclusion: Despite advances in IBD management since 2000, hospitalization rates for persons with IBD are divergent throughout the Western world with over half of countries reporting increases. Newly industrialized countries in South America, the Middle East, and Asia are experiencing rapidly rising hospitalization rates, which is contributing to an increasing burden on global healthcare systems. Table 1. Hospital discharge rates for persons with IBD, by country since 2000 with average annual percent change (AAPC) and associated 95% confidence intervals (CI). Figure 1: IBD Hospitalization rates per 100, 000 at the last available year of data per country.